Evolution of robotic systems for transoral head and neck surgery. (December 2018) - Poon, Howard; Li, Changsheng; Gao, Wenchao; Ren, Hongliang; Lim, Chwee Ming
Highlights: Discuss the historic developments of robots for transoral applications. Present the existing approved robotic systems. Highlight the upcoming robots for transoral robotic surgery. Propose an ideal robot for transoral robotic surgery. Abstract: Oropharyngeal tumor is traditionally resected from an open approach, often necessitating the need of a midline mandibulotomy in order to remove tumor safely with oncologic margins. The limitations imposed by a transoral route include poor visualization of the inferior extent of the oropharynx, rigid instrumentation, and inability to resect tumor that extends caudally into the supraglottis. While visualization with angled endoscopes, coupled with flexible laser development and microscopic magnification may overcome some of these limitations, this technique suffers from linear trajectory of the instruments which hampers expedient surgical resection in a 3-dimensional fashion. With development of the Da Vinci Surgical System, the safety and oncologic feasibility of removing oropharyngeal tumors are made possible because it provides a 3-dimensional magnification of the surgical field and wristed maneuverability of the surgical instruments which enable surgeons to operate around tight anatomical confines. Nevertheless, this first-generation robot is continually being modified with more flexibility and maneuverability through the development of robots like the FLEX Robotic System and more recently the Da Vinci Single Port System (SP). In this review, we will discuss the historic developments of robots for transoral applications, present the current approved robotic systems, and highlight the upcoming robots for transoral robotic surgery (TORS). Finally, we will also propose an ideal TORS surgical robot by highlighting the engineering technologies to accomplish these challenges.